Numerical Analysis of Bumper System Performance in Low and Medium Speed Impacts - Mohammed Mirza Rais Zaihan; Dr. MOHD NORIHAN BIN IBRAHIM @ TAMRIN (Research Progress in Mechanical and Manufacturing Engineering, 2026)
This study uses Finite Element Analysis (FEA) to analyze the performance of bumper systems in low and medium-speed crashes. The study’s goal is to determine how well lightweight materials like aluminum alloy and magnesium alloy absorb impact energy during collisions at speeds of 20 and 40 km/h, respectively. ANSYS was used tosimulate frontal impacts on bumpers against a structural steel wall. The findings demonstrate that, while both materials performed well at low speeds, aluminum alloy outperformed magnesium alloy at medium speeds, demonstrating superior energy absorption and structural integrity. The findings indicate that additional design modifications, such as hybrid materials or reinforced constructions, could increase bumper performance and safety in normal driving circumstances.